Karma, a new genus in the Pleurothallidinae (Orchidaceae) - Karremans Lok, Adam Philip (2023)
The new generic name Karma (Orchidaceae: Pleurothallidinae) is proposed to substitute the concept of Tubella (Luer) Archila [2009], which is illegitimate on account of the prior homonym Tubella Archila [2006], a genus in the Gentianaceae. The latter was proposed together with the illegitimate genus Xenia Archila in the Asclepiadaceae, and the invalid Pseudolepanthes Archila in the Orchidaceae. All three names were “hidden” at the end of an unrelated paper in Revista Guatemalensis volume 2 number 2 and had been forgotten or ignored until now. Taxonomic proposals published in this inconsistent, self-published, cryptic journal are good candidates for suppression, especially given the existence of alternative contents and pre-dated covers, among other issues.